A community study of severe mental retardation in the West Midlands and the importance of the fragile X chromosome in its aetiology. Issue 4 (August 1985) - Bundey, S; Webb, T P; Thake, A; Todd, J
Abstract : This paper describes a community based study of 156 boys with idiopathic, severe mental retardation. The boys were examined and a pedigree taken before the cytogenetic results were known. The prevalence of the fragile X chromosome among this group of boys was high: 9% in the whole group and 11% after 39 boys with specific features had been excluded. The fragile X syndrome is therefore an important cause of idiopathic, severe retardation. Its clinical features of large head, large testes, and IQ in the 35 to 70 range were often but not always present in the 14 boys identified in this study. In the whole group, the recurrence of severe mental subnormality was high: 1 in 8 for brothers and 1 in 25 for sisters. This high recurrence was partly due to the fragile X syndrome, partly to X linked mental retardation not accompanied by cytogenetic abnormalities, and partly due to autosomal recessive disease. Autosomal recessive disease was perhaps higher in the West Midlands than elsewhere (such as British Columbia, for example 1) because of the disproportionate contribution by Asian immigrants.